Public debate in Russia : matters of (dis)order - Vakhtin, N. B. (Nikolaĭ Borisovich); Firsov, B. M. (Edinburgh : Edinburgh Edinburgh University Press, 2016)
An interdisciplinary study of Russian public debate past and present. Can we trace attempts taken in Russian history to overcome the inability to speak publicly? How do different social groups in modern Russia cope with situations when they have to participate in a public discussion and arrive at a compromise? What historic, sociological, linguistic, and psychological reasons underlie intolerance towards different opinions? Can this situation be changed? Bringing together an international team of leading historians, sociolinguists and sociologists in this field, this volume explores these questions from different methodological perspectives, using various sets of data and examining the different domains of private, public and official discourses. Offering detailed case studies of the past and present communicative successes and failures in various social groups, the book explores why Russian society is unable to reach a consensus through dialogue. The first book to offer a detailed exploration of the condition of public debate in Russia, this pioneering volume presents a truly interdisciplinary perspective on Russian language and society making it essential reading for advanced students and specialist in the fields of Slavic Studies, Cultural Studies, Sociolinguistics and Russian history, politics and sociology. Key Features. Presents a pioneering study of Russian public debate Offers a new approach to Russian modernisation through a multidisciplinary view on language and society Includes detailed case studies of the past and present communicative successes and failures in various social groups Brings together an established and international team of contributors from Russia, UK, Israel and France The first book to offer a detailed exploration of the condition of public debate in Russia, this pioneering volume presents a truly interdisciplinary perspective on Russian language and society. Offering detailed case studies of the past and present communicative successes and failures in various social groups, the contributors explore why Russian society is unable to reach a consensus through dialogue.
Introduction: Nikolai Vakhtin, Boris Firsov; Chapter 1: The discourse of argumentation in totalitarian language and post-Soviet communication failures, Nikolai Vakhtin; Chapter 2: Russian and Newspeak: between Myth and Reality, Maxim Krongauz; Chapter 3: 'A Society that Speaks Concordantly' or Mechanisms of Communication of Government and Society in Old and New Russia, Dmitrii Kalugin; Chapter 4: Legal Literature 'for the People' and the Use of Language (Late Nineteenth and Early Twentieth Century), Michel Tissier; Chapter 5: 'How to Write to the Newspapers': Language and Power at the Birth of Soviet Public Language, Catriona Kelly; Chapter 6:The Rhetoric of the Social(ist) Meeting in Literature and Cinema, Valerii V'iugin; Chapter 7: Was Official Discourse Hegemonic? Boris Firsov; Chapter 8: Attempts to overcome 'public aphasia': an analysis of public discussions in Russia at the beginning of the twenty-first century, Boris Gladarev; Chapter 9: Allotment Associations in Search of a New Meaning, Alexandra Kasatkina; Chapter 10: 'Distances of Vast Dimensions ... ': Official versus Public Language (material from meetings of the organising committees of mass meetings and events, January-February 2012), Kapitolina Fedorova; Chapter 11: Insides made public: Talking publicly about personal in post-Soviet media culture (the example of the Fashion Verdict programme), Juliia Lerner, Klavdiia Zbenovich; Chapter 12: Distorted Speech and Aphasia in Satirical Counter-discourse: Oleg Kozyrev's Internet Videos 'Rulitiki', Lara Ryazanova-Clarke; Chapter 13: The Past and Future of Russian Public Language, Oleg Kharkhordin; About the Authors.
Includes bibliographical references and indexes.
Print version record.
JSTOR
Keywords: Die Stadt ohne Juden; Russian language -- Political aspects -- Russia (Federation); Debates and debating -- Russia (Federation); Sociolinguistics -- Russia (Federation); Russia (Federation) -- Social conditions; Russe (Langue) -- Aspect politique -- Russie; Débats et controverses -- Russie; Sociolinguistique -- Russie; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- General; Sociolinguistics; Debates and debating; Social conditions; Russian language -- Political aspects; Russia (Federation); Debatte; Diskurs; Russland